SUPPLY CHAIN DISRUPTIONS AND IMPORT PRICE INFLATION IN IRAQ: EVIDENCE FROM SHIPPING AND CUSTOMS DATA, 2016–2025 - Sahar Kareem Gatae Ali (Antis Publisher, 2026)
Objective: This study investigates the impacts of both supply chain disruption and customs friction on import inflation in Iraq during the monthly period 2016-2025, as an asymmetric response. Method: The study builds three fundamental indicators: import price inflation, disruptions to supply chain, customs friction. An import price inflation index is calculated using the monthly log difference of import unit values, and the composite indices for supply chain disruptions and customs frictions are based on shipping and customs-related indices. The paper uses the nonlinear autoregressive distributed lag model methodologically to account for the nonlinearity in both the short-term and longer-term passage of logistical and customs shocks through import prices. Results: The bounds test results suggest a stable long-run relationship between the variables. Positive supply chain disruptions and positive customs frictions have a larger positive effect on import price inflation than negative changes to the two components have a negative effect. The error correction coefficient is negative and statistically significant, which means that the economy is indeed converging towards the long-run equilibrium, following the short-run shocks. All the diagnostic tests show no serial correlation, heteroskedasticity, ARCH effects, normally distributed residuals, correct functional form, and stable parameters. Novelty: The results indicate that the inflationary pressures in Iraq are not solely imposed by monetary and exchange-rate factors but also arise due to logistical constraints and inefficiencies in customs procedures.